OBTAIN CUCURBITACIN FROM Ecballium elaterium and Cucurbita pepo and CONVERTING INTO A PHARMACEUTICAL FORM - Duran, Derya (Journal of Food and Pharmaceutical Sciences, 2019)
The squirting cucumber plant is widely used in the treatment of sinusitis, rheumatism, and hepatitis. It is reported that the liquid obtained from fruits is widely used in the treatment of sinusitis among people, especially in Turkey. The active components of Nigella sativa seeds are shown to be effective in inflammatory diseases caused by histamine. In this study, it was aimed to create a spray form by extracting Ecballium elaterium and Cucurbita pepo plants, which are easily found in almost every region of Turkey, mixing them with black cumin oil which is used widely and traditionally, and using inactive ingredients. Firstly, the amounts of cucurbitacin D, I, B, E from Ecballium elaterium were determined by HPLC and validation of cucurbitacin active substance analytical method was performed. Physicochemical properties of the nasal spray including pH, osmolality, specific gravity, and viscosity values were determined. Skin irritation, sensitization, and cytotoxicity tests were performed on the final product. The total amount of cucurbitacin D, I, B, E in squirting cucumber was found to be about 4% of the fruit juice. The proportion of these substances was also examined in squash juice and was found to be 0.033% for the respective amount. Skin irritation, sensitization, and cytotoxicity tests were performed in the obtained product and no adverse effects were observed. In addition, physicochemical parameters of the spray, such as pH, osmolality, specific gravity, and viscosity were measured. Results were found as 6.179, 630 mOsmol/L, 55.4 Mpa/s and 1,080 g/cm3 at ph 25 ÂºC, respectively.